Manipulation of oxalate metabolism in plants for improving food quality and productivity. (February 2019) - Kumar, Vinay; Irfan, Mohammad; Datta, Asis
Abstract: Oxalic acid is a naturally occurring metabolite in plants and a common constituent of all plant-derived human diets. Oxalic acid has diverse unrelated roles in plant metabolism, including pH regulation in association with nitrogen metabolism, metal ion homeostasis and calcium storage. In plants, oxalic acid is also a pathogenesis factor and is secreted by various fungi during host infection. Unlike those of plants, fungi and bacteria, the human genome does not contain any oxalate-degrading genes, and therefore, the consumption of large amounts of plant-derived oxalate is considered detrimental to human health. In this review, we discuss recent biotechnological approaches that have been used to reduce the oxalate content of plant tissues. Graphical abstract: Highlights: Oxalic acid is an antinutrient in humans and a pathogenesis factor in plants. Consumption of high oxalate diet may lead to hyperoxaluria and harm renal tissues. Genetically engineered crops for low oxalate content have been developed. Understanding of oxalate metabolism could provide insights for crop improvement.